IMPLEMENTASI PENDEKATAN PERSUASIF DALAM PEMBELAJARAN WUDHU SISWA CEREBRAL PALSY DI RUMAH PINTAR SALATIGA - Dinyati, Dety Vera; Fadli, Muhammad Ulfi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
The purpose of this study is to determine and analyze: the design, implementation, and evaluation of ablution learning for cerebral palsy students at Rumah Pintar Salatiga. The data collection techniques used were interview, observation, and documentation regarding the process of preparation, implementation, and evaluation of ablution learning for inclusion students. The research data collected is in the form of verbal information about the problem that is the focus of the research. Furthermore, data validity is faced by using triangulation techniques. The research data were analyzed in accordance with the facts found in the field. Research analysis as described above is known as qualitative inductive analysis. The results of this study show that 1) The learning design is designed inclusively flexibly and according to the limitations of beginning students. 2) In accordance with the learning design, the implementation of learning for both the initial, core, and final activities of learning for cerebral palsy students is more flexible. 3) Learning evaluation is adjusted to the affordability of students' abilities because the cerebral palsy experienced by students has an impact on various abilities such as rinsing the mouth, washing the face, washing hands, and other ablution movements so that the spirit of learning ablution like anything will always be appreciated by the teacher.